Results of Using Selective Endotoxin Adsorption in Cancer Patients with Sepsis - N. D. Ushakova; A. N. Shevchenko; M. V. Chetverikov; E. Yu. Zlatnik; T. A. Zykova (Общая реаниматология, 2014)
Objective: to study the clinical efficiency of using selective lipopolysaccharide (LPS) adsorption in postoperative gram negative sepsis in cancer patients.Subjects and methods. Examinations were made in 47 patients (11 women and 36 men) aged 47 to 84 years, who had been operated on for cancer and whose postoperative period had been complicated by gramnegative sepsis. The patients were divided into 2 groups: 1) 15 patents who received standard therapy (a control group); 2) 32 who had LPS adsorption using immobilized polymyxin B (a study group).Results. Upon completion of the selective LPS adsorption program, there was regression of the clinical signs of sepsis, statistically significantly lower peripheral blood leukocyte and neutrophil levels, and better blood biochemical parameters in 87.5% of cases. High baseline endotox in activity decreased from >0.6 to <0.4 units in 89% of the patients. After the final session of LPS adsorption, the need for vasopressor support reduced due to hemodynamic profile optimization. After selective endotoxin adsorption cycles, 15 of 26 cases did not need to continue organ replacement therapy. Twentyeightday mortality rates in the study and control groups were 25.0 and 53.3%, respectively.Conclusion. Incorporation of LPS adsorption into a set of intensive therapy for gramnegative sepsis is pathogenetically substantiated and can effectively abolish the manifestations of the systemic effects of bacterial endotoxin. The early and timely use of LPS adsorption provides inhibition of an initiating stimulus, which makes it possible to prevent the progression of a septic process and the development of severe sepsis and septic shock and improves the results of therapy in cancer inpatients.